What role can the Internet play in the development of democracy in Africa? - George Nyabuga (Communicare)
This article explores the recent trends in information technology, specifically the Internet, and what role it can play in the development and sustainability of democracy in Africa. It examines what role it can play in revitalising the public sphere and how it can influence political decisions in the continent. However, I argue that even though the Internet has had profound effects on people’s lives, contributing significantly to communication and information sharing, its real potential is yet to be realised in Africa. This means in effect, that although it might have contributed to various sociological phenomena, it could potentially be dangerous to the growth of democracy in Africa because it is still in the hands of a few, especially those in power. 120 Communicare 23(1) - July 2004 George